Effect of sweptback angle of a delta wing on surface pressure distribution at supersonic Mach numbers - Shetty, Shamitha; Crasta, Asha; Khan, Sher Afghan; Aabid, Abdul; Baig, Muneer (Tech Science Press, 2024)
This work aims to shed light on the effect of the pivot position on the surface pressure distribution over a 3D wing in different flight conditions. The study is intended to support the design and development of aerospace vehicles where stability analysis, performance optimization, and aircraft design are of primary importance. The following parameters are considered: Mach numbers (M) of 1.3, 1.8, 2.3, 2.8, 3.3, and 3.8, angle of incidence (θ) in the range from 5° to 25°, pivot position from h = 0.2 to 1. The results of the CFD numerical simulations match available analytical data, thereby providing evidence for the reliability of the used approach. The findings provide valuable insights into the relationship between the surface pressure distribution, the Mach number, and the angle of incidence.